Indication of Xenia Effect on Cocoa (Theobroma cacao L.) - Indah Anita-Sari; Agung Wahyu Susilo (Indonesian Coffee and Cocoa Research Institute, 2011)
Cocoa plant generally is classified as cross pollinated plant and self-incompatible plant, then there is indication the presence of pollen influence on cocoa bean quality. This study was aimed to determine the effect of pollen sources (xenia) on the colour and size characters of fresh cocoa beans (Theobroma cacao L.). This study was done on two stages. The first stage, a treatment of hand pollination of cocoa clones of DR 1, DR 2, DRC 16, KW 264 and ICCRI 03 was applied in this study. There were five treatments of hand pollination: DR 2 x DR 1, DRC 16 x DR 1, DRC 16 X KW 264, DR 1 x DR 2 and ICCRI 03 x DRC 16. Each treatment was repeated four times. Colour parameters of fresh cocoa beans were observed. The second stage consisted of nine hand pollination combinations: TSH 858 x Sulawesi 1, TSH 858 x ICCRI 03, TSH 858 x KW 264, TSH 858 x KW 570, TSH 858 x Sca 6, Sulawesi 1 x TSH 858, Sulawesi 1 x Sca 6, Sulawesi 1 x KW 570 and KW 516 x Sca 6. Each treatment was repeated three times. Size parameters of fresh cocoa pod and beans were observed. The result showed that hybridization using pollen source from bulk cocoa and DR 1 contributed dark colour to fineflavored cocoa. This colour contribution was showed by the increase in the dark fresh percentage of cocoa beans. On the other hand, hybridization using pollen source from fine-flavored cocoa contributed white and pale colour to bulk cocoa. This light colour contribution was showed by the decrease in the percentage of the dark fresh beans. Xenia effect occured on pod weight, pod length, pod girth, bean weight with pulp per pod and bean weight without pulp per pod which was shown by the hybridization with TSH 858 as female parent and weight bean without pulp per pod shown by the hybridization with THS 858 and Sulawesi 1 as female parent. Key word: Xenia, fresh beans colour, fresh beans size, Theobroma cacao L.